Novel insights into voltage-gated ion channels: Translational breakthroughs in medical oncology - Minas Sakellakis; Sung Mi Yoon; Jashan Reet; Athanasios Chalkias (Taylor & Francis Group, 2024)
ABSTRACTPreclinical evidence suggests that voltage gradients can act as a kind of top-down master regulator during embryogenesis and orchestrate downstream molecular-genetic pathways during organ regeneration or repair. Moreover, electrical stimulation shifts response to injury toward regeneration instead of healing or scarring. Cancer and embryogenesis not only share common phenotypical features but also commonly upregulated molecular pathways. Voltage-gated ion channel activity is directly or indirectly linked to the pathogenesis of cancer hallmarks, while experimental and clinical studies suggest that their modulation, e.g., by anesthetic agents, may exert antitumor effects. A large recent clinical trial served as a proof-of-principle for the benefit of preoperative use of topical sodium channel blockade as a potential anticancer strategy against early human breast cancers. Regardless of whether ion channel aberrations are primary or secondary cancer drivers, understanding the functional consequences of these events may guide us toward the development of novel therapeutic approaches.